2000
DOI: 10.1107/s0907444999015103
|View full text |Cite
|
Sign up to set email alerts
|

A rational approach towards successful crystallization and crystal treatment of human cytomegalovirus protease and its inhibitor complex

Abstract: The crystallization and subsequent crystal treatment of both free human cytomegalovirus (hCMV) protease and its inhibitor complexes are reported. For free-enzyme crystals, diffraction was greatly improved by optimizing the crystallization conditions, raising the precipitant concentration in the reservoir and soaking the crystals in artificial mother liquors. Each of the six components in the final crystallization formula (16% PEG 4000, 0.1 M MES pH 6.0, 0.4 M LiCl, 10% glycerol, 5% t-butanol and 5 mM Na(2)S(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For more challenging target proteins, it may be necessary to increase the number of conditions tested in the initial screen, or to use a larger number of initial target variants to increase the likelihood of obtaining successful crystallization conditions. In addition, a recent report illustrated the stepwise systematic identi®cation and incorporation of additional components into an initial crystallization formulation in order to arrive at ®nal conditions that yielded larger, more well-ordered crystals (Qian et al, 2000); incorporation of additional components is another avenue of exploration that is possible with nanodroplet delivery. The crystallization solution Table 1 Variation in crystallization time (signifying the representative number of hours at which crystal formation is ®rst noted) at various drop volumes (nL) for four proteins at 277 K in custom crystallization plates.…”
Section: Resultsmentioning
confidence: 99%
“…For more challenging target proteins, it may be necessary to increase the number of conditions tested in the initial screen, or to use a larger number of initial target variants to increase the likelihood of obtaining successful crystallization conditions. In addition, a recent report illustrated the stepwise systematic identi®cation and incorporation of additional components into an initial crystallization formulation in order to arrive at ®nal conditions that yielded larger, more well-ordered crystals (Qian et al, 2000); incorporation of additional components is another avenue of exploration that is possible with nanodroplet delivery. The crystallization solution Table 1 Variation in crystallization time (signifying the representative number of hours at which crystal formation is ®rst noted) at various drop volumes (nL) for four proteins at 277 K in custom crystallization plates.…”
Section: Resultsmentioning
confidence: 99%
“…The quest for new inhibitors of HCMV protease 92 has been paralleled by much activity focusing on the structural biology of the target, 93,94 which has elucidated the highly novel structure of this enzime. 95 X-ray crystallographic studies 96 have revealed HCMV protease to possess a protein fold previously unseen among serine proteases as well as a unique catalytic triad (Ser, His, His).…”
Section: Hcmv Protease Inhibitorsmentioning
confidence: 99%
“…Peptides were also derivatized to contain chemically reactive group such as aldehyde or fluoromethylketone to provide an activated carbonyl group that attacks the active site serine hydroxy group to form covalent inhibitor: acyl enzyme complexes [96,109]. Knowledge of key interactions between inhibitors and side chains of amino acids lining the active site learnt from x-ray structures of binary complexes were used to carry out iterative drug design cycles [96,110].…”
Section: Peptidomimeticsmentioning
confidence: 99%